2022
DOI: 10.1136/bmj.o819
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone at home

Abstract: The World Health Organization's new guidelines on abortion care recommend that medical abortion in the first 12 weeks of pregnancy can safely be delivered by telemedicine and that women can self-administer both mifepristone and misoprostol at home. 1Competing interests: We have read and understood BMJ policy on declaration of interests and have no interests to declare.Provenance and peer review: Commissioned; not externally peer reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Mifepristone not only has anti-progestin effects but also affects the hypothalamic-pituitary-ovarian axis. It can act on the hypothalamus to inhibit the secretion of gonadotropin-releasing hormone, affecting FSH and LH secretion, and it can also directly act on the pituitary gland to inhibit FSH and LH release, further lowering serum FSH and LH levels, inducing amenorrhea [17] . Mifepristone's indications have not yet been included in HMB, but studies in AUB caused by AUB-L and AUB-A have observed that low-dose (2.5-10mg) Mifepristone can achieve amenorrhea rates of 41-98.9% [18][19][20][21][22][23][24] , and high-dose (50mg) Mifepristone can achieve a 100% amenorrhea rate [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone not only has anti-progestin effects but also affects the hypothalamic-pituitary-ovarian axis. It can act on the hypothalamus to inhibit the secretion of gonadotropin-releasing hormone, affecting FSH and LH secretion, and it can also directly act on the pituitary gland to inhibit FSH and LH release, further lowering serum FSH and LH levels, inducing amenorrhea [17] . Mifepristone's indications have not yet been included in HMB, but studies in AUB caused by AUB-L and AUB-A have observed that low-dose (2.5-10mg) Mifepristone can achieve amenorrhea rates of 41-98.9% [18][19][20][21][22][23][24] , and high-dose (50mg) Mifepristone can achieve a 100% amenorrhea rate [25] .…”
Section: Discussionmentioning
confidence: 99%